Exploring the motives of appointing independent directors - Abdullah, Shamsul Nahar; Zainal Abidin , Nor Hafizah; Abu Bakar, Intan Suryani; Ur Rahman, Anis (2015)
The aim of this study is to examine the views of chairman and members of nomination committee on motives in appointing an independent director in Malaysian public listed companies. Semi-structured interview was used and 21 directors were interviewed. The results indicate that independent directors were expected to execute their monitoring role, exercise unbiased judgment in questioning decisions made and safeguard balance of power between the board and management. In addition, the respondents believe that independent director should utilize their capacity from related background, expertise and experience in board meeting discussion in addressing issues or risks and making relevant suggestions.